Kandungan Protein dan Kadar Air Bakso Daging Ayam Broiler pada Penambahan Bahan Pengenyal yang Berbeda - Rusli, Rusli; Novieta, Intan Dwi; Rasbawati, Rasbawati (bionature, 2019)
Abtract. The study aimed to determine the effect of different meatball enhancers on meatbel protein and to determine the effect of different meatball enhancers against meatball water content. This research was conducted in june 2018 at the Laboratory of the Faculty of Agriculture, Animal Husbandry and Fisheries of the University of Muhammadiyah Parepare. Research using broiler chicken meat, water, flavorings, garlic, pepper, salt, egg white, carrageenan, gelatin, tissue, and ice cubes. The study used a completely randomized design (CRD) with four treatment levels and three replications, namely T0 = without ingreadients, T1 = crisp egg white, T2 = crustacean, T = gelatin. The results of the study showed that with the addition of pulses that the protein content of meatballs had a very real effect and water content in meatball with the addition of different ingredients that are influential real to meatball water content. The highest average protein value to the lowest is T0 is 6.52, T2 is 6.46, T1 is 6.33, T3 is 4,15. The highest average water volues to the lowest were T1 at 63.35, T0 at 63.05, T3 at 62.58, and T2 at 62.44. From the results of the study, it is known that the best treatment and can be recommended is T2 treatment with karagenan crusher.Keywords: Proteins, water content, broiler chicken meat, egg white, carrageenan, and gelatin.